2020
DOI: 10.1111/jfpp.14980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grape variety on bioactive compounds, antioxidant activity, and phenolic compounds of some grape seeds grown in Turkey

Abstract: Grape (Vitis vinifera) are widely planted in the world and it is one of largest agricultural crops. The most these common cultivars of grape in Turkey. Turkey has a very rich genetic potential in grapes due to varying climatic conditions, and is one of the world's leading grape producers. Grape seeds are rich in phenolic compounds, and their constituents such as gallic acid, syringic acid, and epicatechin are the main phenolic compounds which an important role as defense compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Comparing the obtained values with those in the literature [44][45][46], it is possible to affirm that the values are similar to those reported. The slight distinction of the values can be associated with the variety of grape used, maturation phase, cultivation conditions, extraction conditions, among other variables.…”
Section: Dpph (% Dpph Inhibition)supporting
confidence: 88%
“…Comparing the obtained values with those in the literature [44][45][46], it is possible to affirm that the values are similar to those reported. The slight distinction of the values can be associated with the variety of grape used, maturation phase, cultivation conditions, extraction conditions, among other variables.…”
Section: Dpph (% Dpph Inhibition)supporting
confidence: 88%
“…Dedebas et al (2020) reported antioxidant activity of 4.89 mM equivalent of Trolox (1.292 µg•mL -1 ) for grapeseed oil obtained by cold pressing and stored at 20 °C. Ghafoor et al (2020) reported antioxidant activities in the range of 78-92% of ABTS •+ scavenging for several grape seed oils from Turkey. On the other hand, Li et al (2020) reported an antioxidant activity of 13.0 µM equivalent of Trolox for grape seed oil obtained by Soxhlet extraction with hexane.…”
Section: Seed Oil Antioxidant Activitymentioning
confidence: 99%
“…Phenolic extracts have shown higher antimicrobial potency than pure phenolic compounds [ 17 ]. The reason for this may be that there is a synergistic effect between the components of the extracts [ 18 ]. This is why it is important to study the phenolic content and composition of GSEs and their correlation with antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%